UJI ANTIOKSIDAN EKSTRAK DAN FORMULASI SEDIAAN KRIM TABIR SURYA KULIT DELIMA PUTIH (Punica granatum L.) DENGAN METODE DPPH DAN PENENTUAN NILAI SPF - Vanny (PC IAI Sragen, 2023)
White Pomegranate (Punica granatum L.) is a plant that is efficacious as an antioxidant which functions as a natural antioxidant to prevent free radicals from harming the body because it contains flavonoid compounds including flavones and flavonols which are known as natural antioxidants. This study aims to determine the IC50 value of extracts and formulations of white pomegranate skin sunscreen cream (Punica granatum L.) along with its SPF value. The extract was prepared by maceration using 96% ethanol. Testing the antioxidant activity of white pomegranate peel extract (Punica granatum L.) using UV-Vis spectrophotometry with the DPPH method (1,1-Diphenyl-2-Picrylhyrdazyl), the test results showed that white pomegranate peel extract (Punica granatum L.) had an IC50 value of 92,76 ppm in the strong category. Sunscreen cream was made into four formulas, namely F0, FI, FII and FIII with extract concentrations of 5%, 10% and 15% respectively. The physical evaluation was tested, including organoleptic test, homogeneity test, cream type test, spreadability test, adhesion test, pH test, viscosity test and organoleptic stability test which showed that the four formulas met the requirements of the physical evaluation test for sunscreen cream preparations. The four sunscreen cream formulas, an antioxidant activity test was carried out using the DPPH method (1,1-Diphenyl-2-Picrylhyrdazyl) at F0, FI, FII and FIII and obtained IC50 values ​​of 146,9 ppm (weak), 98,22 ppm (strong), 81,37 ppm (strong) and 76,88 ppm (strong). Determination of the SPF (Sun Protection Factor) value was carried out using the mansyur equation method using UV-Vis spectrophotometry at a wavelength of 290-320 nm. The results obtained for the SPF values ​​in the four formulas F0, FI, FII and FIII were 6,02 (extra), 14,39 (maximum), 22,98 (ultra) and 27,60 (ultra).